1993
DOI: 10.1017/s0813483900005581
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcome of Anorexia Nervosa

Abstract: The long-term outcome (mean follow-up period 5.7 years) for 20 patients with anorexia nervosa was assessed on a comprehensive battery of self-report inventories and a structured clinical interview. Two thirds of the cohort were improved to a clinically significant degree at follow-up, but the majority still showed higher than normal scores on inventories of anorexic symptomatology, social maladjustment, anxiety, and hostility. The remaining one third were unimproved and demonstrated a broad range of impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This indicated that our patients with poor outcome took more time from the onset of illness to referral. A number of studies have suggested that a large interval between the time of onset and first admission for treatment may be negatively related to the outcome of treatment 29–31 . These findings suggest that patients older than 20 years at onset and with a longer time from the onset to referral may be associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that our patients with poor outcome took more time from the onset of illness to referral. A number of studies have suggested that a large interval between the time of onset and first admission for treatment may be negatively related to the outcome of treatment 29–31 . These findings suggest that patients older than 20 years at onset and with a longer time from the onset to referral may be associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Typically this relationship is articulated as one of less control with advancing chronicity, although the mechanisms inducing this are described differently by different models (Surgenor, Horn, Plumridge, & Hudson, 2002). Finally, psychological control constructs have been suggested as prognostic indicators (Hood, Moore, & Garner, 1982;Jones, Halford, & Dooley, 1993) and predictors of treatment response (Strober, 1982) and menstrual status (Swain, Shisslak, & Crago, 1991). These views are also to be found in theoretical accounts.…”
Section: Introductionmentioning
confidence: 99%
“…Poor outcome in anorexia nervosa and bulimia nervosa has been associated with a number of prognostic indicators. These include longer duration of illness, increased severity of symptoms, poor motivation for therapy, failure of previous treatment, chronicity, and psychiatric comorbidity (Herzog, Keller, & Lavori, 1988;Herzog, Nussbaum, & Marmor, 1996;Jones, Halford, & Dooley, 1993;Pollice, Kaye, Greeno, & Weltzin, 1997;Schoemaker, 1997;Treasure, 1991). Several of the aforementioned indicators are typically present in eating-disordered patients with a history of recalcitrance or resistance to treatment, and poor outcome is common in this population (Hamburg, Herzog, & Brotman, 1996;Hamburg, Herzog, Brotman, & Stasior, 1989;Yager, 1992).…”
Section: Discussionmentioning
confidence: 99%